2020
DOI: 10.3390/nu12072031
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Protein Intake and Source on Factors Associated with Glycemic Control in Individuals with Prediabetes and Type 2 Diabetes

Abstract: Type 2 diabetes (T2D) is a major contributor to morbidity and mortality largely due to increased cardiovascular disease risk. This study examined the relationships among protein consumption and sources on glycemic control and cardiovascular health in individuals with prediabetes and T2D. Sixty-two overweight or obese participants with prediabetes or T2D, aged 45–75 years were stratified into the following three groups based on protein intake: <0.8 g (gram)/kg (kilogram) body weight (bw), ≥0.8 but &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…This shows that β-cell function can be improved by increasing animal protein intake. 5 Our results did not classify the individual’s protein intake according to source (ie, animal or plant protein) or measure the β-cell function.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…This shows that β-cell function can be improved by increasing animal protein intake. 5 Our results did not classify the individual’s protein intake according to source (ie, animal or plant protein) or measure the β-cell function.…”
Section: Discussionmentioning
confidence: 66%
“…Evidence proposes that high-protein intake is associated with an improvement in insulin resistance; however, the lipid profiles were not affected in the study population. 5 Furthermore, Akhavan et al (2020) reported that a higher intake of animal protein can enhance the function of β-cell and reduce plasma triglycerides.…”
Section: Introductionmentioning
confidence: 99%
“…However, it’s important to note that more clinical trials need to be conducted to confirm the effects of specific nutrients on diabetes and mental health outcomes when they coexist. It has been shown that individuals with diabetes who follow a specialized diet can maintain the best glycemic control and decrease the chance of diabetes-related complications [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. In addition, the poor nutritional intake of essential nutrients can impact the body’s ability to produce hormones and neurotransmitters and further influence blood glucose levels and mental health [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…A randomized crossover study on eight patients with T2DM showed that a high-protein-low-CHO diet improves glycemic control with statistically significant results [ 165 ]. A recent cross-sectional study of 212 participants (most participants were between the ages of 45 and 75, overweight or obese, with prediabetes or T2DM) suggested that the mean value of HOMA-IR is lower in those with a protein intake higher than recommendations as compared to those whose protein intake was lower [ 166 ]. A meta-analysis of 9 short-term studies (418 subjects with T2DM) showed that high-protein diets resulted in a better glycemic control (decreased HbA1c by 0.52%) and weight loss but did not affect fasting blood glucose or lipid levels [ 167 ].…”
Section: Macronutrientsmentioning
confidence: 99%